Enhanced gas production by forming artificial impermeable barriers from unconfined hydrate deposits in Shenhu area of South China sea. (15th December 2020) - Zhao, Ermeng; Hou, Jian; Liu, Yongge; Ji, Yunkai; Liu, Wenbin; Lu, Nu; Bai, Yajie
Abstract: The absence of impermeable overburden and underburden layers makes it difficult to develop the unconfined hydrate deposits. Using numerical simulation method, the hydrate dissociation and gas production behaviors are fully investigated during depressurization in Shenhu Area based on the available geological data. Results show that depressurization cannot result in significant pressure drop due to the presence of permeable boundaries, which leads to low gas production rate but excessive water production. To overcome these disadvantages, the method of forming artificial impermeable barriers by injecting gels in the permeable overburden and underburden is proposed in this work. Moreover, the effect of the radius of artificial impermeable barriers on gas production is analyzed numerically. Simulation results show that the artificial impermeable barriers prevent large amounts of seawater from entering the production well during the depressurization process, which significantly enhances the depressurization effect, and thus promotes hydrate dissociation and gas production. By forming the 90-m artificial impermeable barriers, the hydrate dissociation percent is greatly enhanced from 8.9% to 45.4%, the cumulative CH4 production volume is increased from 4.46 × 10 6 ST m 3 to 1.06 × 10 7 ST m 3, while the average water production rate is remarkably decreased from 1412 m 3 /d to 360 m 3 /d. Highlights: Gas production from unconfined hydrate deposits is investigated with numerical simulation method. The method of forming artificial impermeable barriers by injecting gels is proposed. Depressurization is significantly enhanced after forming artificial impermeable barriers. Hydrate dissociation percent is greatly enhanced from 8.9% to 45.4%.